2016
DOI: 10.3390/w8090394
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Course and Frequency of High Water Stages in Selected Catchments of the Upper Vistula Basin in the South of Poland

Abstract: Abstract:The paper presents an analysis of the course and frequency of high water stages in selected catchments of the upper Vistula basin in the south of Poland. The following rivers were investigated: the Dunajec-Nowy Targ-Kowaniec cross-section, the Rudawa-Balice cross-section, the Kamienica-Nowy Sącz cross-section, the Wisłok-Tryńcza cross-section and the San-Przemyśl cross-section. Daily flows from the years 1983-2014 were used to determine maximum annual flows and maximum flows per summer and winter half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 26 publications
(23 reference statements)
3
12
0
Order By: Relevance
“…Therefore, in the analysed multi-year period, no factor has appeared that would significantly affect the course of processes shaping flood flows from these catchments. Similar research results related to the analysis of changes in the flood flows from the catchments of the upper Vistula river basin are presented in the papers [35,36], where in the majority of the studied cases there were also no statistically significant trends found in the observation series of flood flows in the upper Vistula basin. Bearing in mind that the observation series adopted for further analysis should meet the requirements of a simple random sample, the following catchments were excluded from further research: Bystra-Kamesznica, Skawica-Zawoja, Stryszawka-Sucha, Raba-Rabka, and Grajcarek-Szczawnica.…”
Section: Statistical Verification Of Datasupporting
confidence: 77%
“…Therefore, in the analysed multi-year period, no factor has appeared that would significantly affect the course of processes shaping flood flows from these catchments. Similar research results related to the analysis of changes in the flood flows from the catchments of the upper Vistula river basin are presented in the papers [35,36], where in the majority of the studied cases there were also no statistically significant trends found in the observation series of flood flows in the upper Vistula basin. Bearing in mind that the observation series adopted for further analysis should meet the requirements of a simple random sample, the following catchments were excluded from further research: Bystra-Kamesznica, Skawica-Zawoja, Stryszawka-Sucha, Raba-Rabka, and Grajcarek-Szczawnica.…”
Section: Statistical Verification Of Datasupporting
confidence: 77%
“…Insignificant trends observed for the majority of weather stations in our study reflected the course of high water in the catchments of the Upper Vistula Basin. Research conducted by Kundzewicz et al [46], Wałęga et al [47], and Młyński et al [48] showed a stable runoff of high water in the catchments of the Upper Vistula Basin in recent decades. Flood size in this region depends on multiple factors such as geology, soils, geomorphological evolution, landscape structure, or land use.…”
Section: Significant Verification Of the Trend For The Annual Maximummentioning
confidence: 99%
“…Increased winter precipitation in the mountains raises the flooding risk, even if the coincidental rise in air temperature increases the frequency of rainfall instead of snowfall. The increased frequency of high water stages has been reported by Walega et al (2016). Climate change projection also suggests that changes in cyclone track may increase the extreme precipitation events (Nissen et al 2013).…”
Section: Discussionmentioning
confidence: 86%
“…The changes of thermal regime means, among others, shorter winters and changes of precipitations forms with greater proportion of mixed and liquid precipitation, especially in winter (Twardosz et al 2012;Taskinen and Söderholm 2016). For solid precipitation, gauge undercatch at the same wind speed is higher than for rain (Wagner 2009), so the observed increase in November-March precipitation sums in the Sudetes may be partly caused by lesser measurement losses in changing thermal conditions.…”
Section: Discussionmentioning
confidence: 90%